Sustainable Finance. (29th October 2022) - Edmans, Alex; Kacperczyk, Marcin
Abstract: Sustainable finance—the integration of environmental, social, and governance ("ESG") issues into financial decisions—is an increasingly important topic. Within companies, sustainability is no longer an ancillary issue confined to corporate social responsibility departments, but a CEO-level issue fundamental to the core business. Within the investment industry, sustainability used to be the exclusive domain of "socially responsible investors" who had social as well as financial objectives, but is now mainstream and includes investors with purely financial goals. This article introduces the RF Special Issue on Sustainability. It highlights three reasons for the rapid rise in sustainable finance—its financial relevance, its contribution to nonfinancial objectives, and investor tastes. It then summarizes the eight articles in the Special Issue, in particular drawing out their contributions to the literature. Finally, we offer ideas for future research.